2006
DOI: 10.1093/pcp/pcj023
|View full text |Cite
|
Sign up to set email alerts
|

The Chloroplast Protein Disulfide Isomerase RB60 Reacts with a Regulatory Disulfide of the RNA-binding Protein RB47

Abstract: Biochemical studies have identified two proteins, RB47 and RB60, that are involved in the light-regulated translation of the psbA mRNA in the chloroplast of the unicellular alga Chlamydomonas reinhardtii. RB47, a member of the eukaryotic poly(A)-binding protein family, binds directly to the 5' untranslated region of the mRNA, whereas RB60, a protein disulfide isomerase (PDI), is thought to bind to RB47 and to modulate its activity via redox and phosphorylation events. Our present studies show that RB47 forms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…A redox-active site monothiol mutant, in which the resolving Cys is replaced with a Ser or an Ala, is typically used to inhibit the second step and to increase the stability of the reaction intermediate ( Figure 1B). This approach facilitated the isolation in vivo (Walker et al, 1996;Frand and Kaiser, 1999;Senkevich et al, 2002) or in vitro (Motohashi et al, 2001;Balmer et al, 2003) of Trx targets and the identification in vitro of the Cys residues participating in the intermolecular disulfide (Alergand et al, 2006). Importantly, protein disulfide isomerase (PDI) and its oxidizing protein, ENDOPLASMIC RE-TICULUM OXIDOREDUCTIN1 (ERO1), were trapped by this approach in an intermolecular disulfide complex in yeast and human cells (Pollard et al, 1998;Frand and Kaiser, 1999;Mezghrani et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A redox-active site monothiol mutant, in which the resolving Cys is replaced with a Ser or an Ala, is typically used to inhibit the second step and to increase the stability of the reaction intermediate ( Figure 1B). This approach facilitated the isolation in vivo (Walker et al, 1996;Frand and Kaiser, 1999;Senkevich et al, 2002) or in vitro (Motohashi et al, 2001;Balmer et al, 2003) of Trx targets and the identification in vitro of the Cys residues participating in the intermolecular disulfide (Alergand et al, 2006). Importantly, protein disulfide isomerase (PDI) and its oxidizing protein, ENDOPLASMIC RE-TICULUM OXIDOREDUCTIN1 (ERO1), were trapped by this approach in an intermolecular disulfide complex in yeast and human cells (Pollard et al, 1998;Frand and Kaiser, 1999;Mezghrani et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Of the three precursor proteins, only the two with internal His tags were recognized without or with thrombin cleavage (compare lanes 1 and 2 with 5/9 and 6/10, respectively). We found that the signal from the internally tagged proteins was completely lost after incubation with chloroplast lysate, with or without thrombin cleavage (lanes 7,8,11,12). This suggested that the 47 kDa species was created by excising sequences within or upstream of the Sph His tag, and within or downstream of the Bsp His tag, and that the higher molecular weight bands in the splicing reactions all were species lacking the NCL, most likely aggregates with different degrees of resistance to SDS denaturation.…”
Section: Resultsmentioning
confidence: 94%
“…RB47 had been discovered previously in Chlamydomonas chloroplasts through affinity purification of proteins binding to the psbA mRNA 5Ј-UTR (7,8). Based on a variety of correlative experiments, RB47 was proposed to regulate psbA translation in response to light (9 -11) and redox poise (12). RB47, for which the isolated cDNA encoded a protein of 68 kDa (80 kDa by SDS-PAGE), could be converted during in vitro chloroplast import to the 47 kDa size found in chloroplasts (7), a difference far in excess of what can be accounted for by removal of the short N-terminal transit peptide (8).…”
mentioning
confidence: 99%
“…Oxidized cysteines represent the off state of the repressor, whereas reduced cysteines represent the on state. It has already been shown that RRM containing proteins from plant organisms involved in translational regulation of photosynthetic genes can be activity-regulated via cysteine modification (13). However, these proteins were shown to be located in the plastid.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid pGDNG1 was constructed by inserting the Wt NAB1 gene into the NdeI and EcoRI cloning sites of plasmid pGenD (13). The plasmids pGDNG1/Cys(181/226Ser), pGDNG1/ Cys(181Ser), and pGDNG1/Cys(226Ser) were generated by site-specific replacement of thymine by adenine at positions 541 and 676 of the NAB1 gene in plasmid pGDNG1 (QuikChange Site-Directed Mutagenesis Kit; Stratagene.…”
Section: Methodsmentioning
confidence: 99%